Gendering Justice in the Chilean Courts: Institutional Developments and Legal Actors’ Perspectives. - Parodi, Karime (Latin American Research Review, 2025)
This article examines how, why, and with what limitations judges have adopted a gendered perspective (perspectiva de género) in Chile. It addresses why the Supreme Court’s Secretariat of Gender and Nondiscrimination advocates for a particular understanding of the concept, how judges understand and apply it, and the barriers they perceive to its implementation. Drawing on interviews, ethnographic fieldwork, and analysis of court rulings, the study identifies four ways in which judges understand a "gendered perspective": as a method to detect stereotypes, a tool to analyze context, an instrument to reach a fair result, and a rejection of the notion of loosening evidentiary standards. The article argues that in contemporary Chile, different legal cultures shape disparate understandings about a gendered perspective. There is significant contestation between understandings endorsed by the dominant textualist legal culture and those favored by the emerging interpretive legal culture. By illuminating the limitations Chilean judges face in this evolving area of the law, the study contributes insights of relevance for our understanding of the factors that affect gender and judging in Latin America and beyond.